Tigroid pattern of cerebral white matter involvement in chromosome 6p25 deletion syndrome with concomitant 5p15 duplication - Balasubramanian, Meena; Smith, Kath; Williams, Steve; Griffiths, Paul D.; Parker, Michael J.; Mordekar, Santosh R. (Journal of Pediatric Genetics, 2012)
Sub-telomeric deletions of the short arm of chromosome 6 are a well-described clinical entity characterized by developmental impairment, hypotonia, eye abnormalities and defects in the heart and kidneys. Chromosome 5p terminal duplication is a rarer entity, associated with developmental impairment and facial dysmorphism. We report a 3-year-old patient with a chromosome 6p25.1pter deletion and chromosome 5p15.1pter duplication who had global developmental impairment and unusual cerebral white matter changes, with hypoplastic corpus callosum and cerebellar vermis on magnetic resonance imaging -brain scan. We discuss the differential diagnosis to consider in patients with this appearance on magnetic resonance imaging -brain scan and reiterate the need for chromosome analysis in patients with this pattern of developmental anomaly. Tigroid pattern of cerebral white matter involvement has not been reported in chromosomal deletion/duplication syndromes. With the increasing use of molecular karyotyping for patients with multiple congenital anomalies and developmental delay, it is important to consider the exact size and nature of chromosomal deletion/duplication, in order to provide families with prognostic information and recurrence risk. This in turn, will help provide valuable information regarding the natural history of rare chromosomal imbalances.
Keywords: Karyotype; array CGH; tigroid appearance; developmental delay; recurrence risk